Uma proposta de um material potencialmente significativo para o estudo de física do primeiro ano do ensino técnico para os cursos de mecatrônica, eletrônica. Eletrotécnica e áreas afins - Oliveira, José Francisco (2019)
The dissertation presents the report of an instructional material MI, applied to the students of the 1st year of Technical High School. The topics presented here, vectors, gravitational field, electric field and electric potential, are collected in the textbooks analyzed, adopted by the National Book and Teaching Material Program (PNLD 2015). However, for the student of Technical Education, some subjects such as Electric Field and Electrical Potential are necessary already in the first year of the course and these same subjects are charged in the PNLD books, only in the third year. In order to assist the work of the first year teachers of the technical courses, this MI was prepared, but inserting the concepts of electric field and electric potential at the beginning of the course and not only of the third year. This material was elaborated based on the theoretical aspects of Ausubel's Significant Learning Theory.